An insight into the use of cannabis in medical and veterinary dermatological applications and its legal regulation - Mišič, Jančar Jakob (2024)
Cannabis contains more than 140 cannabinoid compounds, of which cannabidiol andtetrahydrocannabinol are the most exposed ones, as they have the potential for numerousapplications in various fields of health and medicine. Many scientific findings andnumerous clinical studies over the last decade report results related to pain relief,treatment of chronic diseases and certain neurological disorders in human medicine. Inline with the growing trend of research and application in human medicine, the researchand application potential in veterinary medicine is also increasing. Of the biologicallyactive molecules contained in the plant, cannabidiol has attracted the most interest. Thecultivation of cannabis for medical and pharmaceutical purposes requires, among otherthings, compliance with legal regulations. An analysis of the legal acts regulating the usefor medical and pharmaceutical purposes shows that the current regulation at state levelis complex and should be amended.